Laksana khatyaeng (contrast) nai wannakam ruang Phra `Aphaimani khong Sunthon Phu - Niphon `Insin.; Sunthon Phu, 1786-1855.; Witthayalai Khru Sakon Nakhon. Phak Wicha Phasa Thai. ([Sakon Nakhon] : Phak Wicha Phasa Thai, Khana Manutsayasat lae Sangkhommasat, Witthayalai Khru Sakon Nakhon, 1978)
Textbook on study of contrast in Sunthon Phu's Phra `Aphaimani.
Keywords: Thai literature -- 19th century -- History and criticism